Comparison of Efficacy of Labetalol Versus Alpha Methyldopa in the Management of Preeclampsia - Taj, Tooba Zukhruf; Mehsud, Naseem Saba; Hashmi, Irum Batool; Ayyub, Hina (Indus Journal of Bioscience Research, 2025)
Background: Preeclampsia is a hypertensive disorder that occurs after 20 weeks of gestation and is known to be one of the major causes of morbidity for mothers and their fetuses. The regulation of blood pressure is important in order to prevent severe consequences for mothers and their fetuses. Objective: To compare the efficacy of labetalol and alpha methyldopa in management of preeclampsia. Study Design: Randomized controlled trial. Duration and Place of Study: This study was conducted from 10 April 2024 to 10 October 2024 in Department of Obstetrics and Gynaecology, Zanana Hospital, Dera Ismail Khan. Methodology: A total of 190 women aged 18 to 40 years with singleton pregnancy more than 30 weeks and diagnosed preeclampsia were included. Patients were randomly divided into two equal groups. Group A received labetalol 100 milligram twice daily and Group B received alpha methyldopa 250 milligram three times daily. Efficacy was defined as blood pressure less than 140/90 millimeter of mercury within 48 hours without dose escalation. Data were analyzed using Statistical Package for Social Sciences version 26. Results: Mean age was 29.03 ± 6.36 years in labetalol group and 29.37 ± 7.32 years in alpha methyldopa group. Efficacy was achieved in 81 (85.3%) patients receiving labetalol and 67 (70.5%) receiving alpha methyldopa, showing significant difference (p = 0.014). Conclusion: Labetalol was more effective than alpha methyldopa for controlling blood pressure in preeclampsia.